Rare subungual amelanotic melanoma presenting as prolonged swelling and exudation after trauma: case report and literature review - An, Lin; Liu, Ziyu; Chen, Xiangru; Jia, Yuxi (Frontiers in Immunology, 2025)
BackgroundSubungual amelanotic melanoma (SAM) poses significant diagnostic challenges due to its rarity and nonspecific clinical manifestations, such as nail dystrophy or indurated plaque.Case presentationWe present the case of a 60-year-old woman with a three-year history of recurrent serous drainage and persistent pain in her left middle finger following an initial crush injury. Over a period of two years, she underwent three nail avulsion procedures, received systemic antibiotic therapy, and was treated with topical Chinese herbal therapies under a presumptive diagnosis of “chronic onychia following trauma” at a local hospital. Additionally, PET-CT imaging demonstrated localized inflammatory changes without evidence of neoplastic disease. Despite these interventions, the lesion remained refractory to treatment. A thorough reevaluation conducted by our department, incorporating histopathological and immunohistochemical analyses, ultimately confirmed the diagnosis of SAM.ConclusionsThis case underscores the importance of maintaining a high index of suspicion for SAM when evaluating atypical nail lesions. A low threshold for nail biopsy in cases of prolonged swelling and exudation of a single nail is advised. Additionally, prior trauma to the nail may contribute to the development of SAM through post-traumatic immunosuppression and persistent low-grade chronic inflammation. However, the exact role of trauma in the pathogenesis of melanoma remains unclear and requires further investigation.